Who's in the mirror: shaping organizational identity through artificial intelligence and symbolic interactionism - Canbul Yaroglu, Aslihan (EMERALD GROUP PUBLISHING LTD, 2026)
Purpose - The purpose of this study is to examine the effects of artificial intelligence (AI) on the identity formation processes of individuals and organizations. Within the framework of symbolic interactionism and looking-glass self-theories, it is investigated how AI transforms social interactions and identity perceptions. The study aims to understand how AI reshapes individuals' self-perception in the organizational context and to provide a theoretical explanation of these processes. Design/methodology/approach - This article uses qualitative research and a grounded theory approach to examine the effects of artificial intelligence on individual and organizational identity. Data obtained through literature review and thematic analysis are analyzed to theoretically explain the effects of artificial intelligence on identity formation processes. With the grounded theory method, new theoretical implications are presented regarding the effects of artificial intelligence on identity and social roles. Findings - AI reshapes individual and organizational identities by automating routine tasks and providing rapid feedback, which enhances self-perception and collective identity while potentially introducing identity threats or development opportunities depending on task alignment. Originality/value - This article provides a novel perspective by integrating symbolic interactionism and the looking-glass self-theories with AI interactions, offering fresh insights into how AI affects identity construction in both individuals and organizations. It uniquely examines the dynamic influence of AI on self-perception and organizational identity, contributing to the understanding of AI's role in identity reconfiguration and the cognitive processes behind it.
Keywords: Organizational identity; Artificial intelligence; Symbolic interactionism; Mirror neurons; Self-perceptions; DIGITAL TRANSFORMATION; DECISION-MAKING; TECHNOLOGY; MANAGEMENT; SELF; AI; CONSTRUCTION; BUSINESS; IMPACT; INDIVIDUALS; Computer Science